Augmented Cardiac Growth Hormone Signaling Contributes to Cardiomyopathy Following Genetic Disruption of the Cardiomyocyte Circadian Clock - Sonkar, Ravi; Berry, Ryan; Latimer, Mary N.; Prabhu, Sumanth D.; Young, Martin E.; Frank, Stuart J. (Frontiers in Pharmacology, 2022)
Circadian clocks regulate numerous biological processes, at whole body, organ, and cellular levels. This includes both hormone secretion and target tissue sensitivity. Although growth hormone (GH) secretion is time-of-day-dependent (increased pulse amplitude during the sleep period), little is known regarding whether circadian clocks modulate GH sensitivity in target tissues. GH acts in part through induction of insulin-like growth factor 1 (IGF1), and excess GH/IGF1 signaling has been linked to pathologies such as insulin resistance, acromegaly, and cardiomyopathy. Interestingly, genetic disruption of the cardiomyocyte circadian clock leads to cardiac adverse remodeling, contractile dysfunction, and reduced lifespan. These observations led to the hypothesis that the cardiomyopathy observed following cardiomyocyte circadian clock disruption may be secondary to chronic activation of cardiac GH/IGF1 signaling. Here, we report that cardiomyocyte-specific BMAL1 knockout (CBK) mice exhibit increased cardiac GH sensitivity, as evidenced by augmented GH-induced STAT5 phosphorylation (relative to littermate controls) in the heart (but not in the liver). Moreover, Igf1 mRNA levels are approximately 2-fold higher in CBK hearts (but not in livers), associated with markers of GH/IGF1 signaling activation (e.g., p-ERK, p-mTOR, and p-4EBP1) and adverse remodeling (e.g., cardiomyocyte hypertrophy and interstitial fibrosis). Genetic deletion of one allele of the GH receptor (GHR) normalized cardiac Igf1 levels in CBK hearts, associated with a partial normalization of adverse remodeling. This included attenuated progression of cardiomyopathy in CBK mice. Collectively, these observations suggest that excessive cardiac GH/IGF1 signaling contributes toward cardiomyopathy following genetic disruption of the cardiomyocyte circadian clock.